Kenmotsu pseudo-Riemannian manifolds - Liu, Ximin (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we study some properties of Kenmotsu manifolds with pseudo-Riemannian metrics. We prove that this kind of manifolds satisfying certain conditions such as R(X; Y ) R = 0;R(X; Y ) S = 0 are Einstein manifolds. Also some sucient conditions for a Kenmotsu pseudo-Riemannian metric manifold to be Einstein are obtained.